2017
DOI: 10.1021/acscentsci.7b00026
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Activation of Duocarmycin–Antibody Conjugates by Near-Infrared Light

Abstract: Near-IR photocaging groups based on the heptamethine cyanine scaffold present the opportunity to visualize and then treat diseased tissue with potent bioactive molecules. Here we describe fundamental chemical studies that enable biological validation of this approach. Guided by rational design, including computational analysis, we characterize the impact of structural alterations on the cyanine uncaging reaction. A modest change to the ethylenediamine linker (N,N′-dimethyl to N,N′-diethyl) leads to a bathochro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
169
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(171 citation statements)
references
References 67 publications
2
169
0
Order By: Relevance
“…Our prior studies have suggested that installing a charged functional group proximate to the C4’-position of cyanine polyene serves to mitigate the formation of undesirable H-aggregates, a common issue with these molecules. 15, 22, 23 To introduce this charge, as well as to provide net-netural molecules, we installed a trimethylalkyl-ammonium ether at the C4’ position. To examine the role of the alkyl linker, we have prepared both propyl and ethyl variants.…”
mentioning
confidence: 99%
“…Our prior studies have suggested that installing a charged functional group proximate to the C4’-position of cyanine polyene serves to mitigate the formation of undesirable H-aggregates, a common issue with these molecules. 15, 22, 23 To introduce this charge, as well as to provide net-netural molecules, we installed a trimethylalkyl-ammonium ether at the C4’ position. To examine the role of the alkyl linker, we have prepared both propyl and ethyl variants.…”
mentioning
confidence: 99%
“…In the absence of irradiation with NIR light, the linker‐drug module showed high stability in solution ( t 10 % =230 h), while the photorelease mechanism occurred with a half‐life of 90 min. The linker–drug module conjugated to the anti‐EGFR mAb panitumumab ( 49 ) showed promising anticancer activity in mice xenografted with MDA‐MB‐468 cancer cells . ADC 49 was evaluated in combined therapy with a second mAb conjugated to a photoabsorber (i.e.…”
Section: When and Where: Linker Cleavage Promoted By External Stimulimentioning
confidence: 99%
“… A) Examples of π‐extended photosensitive linkers, cleavable by either two‐photon (TP, as compound 47 ) or single‐photon (SP, compound 48 ) excitation with NIR wavelengths. B) ADC 49 developed by Schnermann and co‐workers, based on a NIR light‐sensitive cyanine linker, a duocarmycin (Duo) payload and a diamine‐based self‐immolative spacer (depicted in green) …”
Section: When and Where: Linker Cleavage Promoted By External Stimulimentioning
confidence: 99%
“…Chemical [70], near-infrared light [71] and tumor microenvironment-triggered payload release strategies have also shown promising results. There is probably no universal conjugate-linkage strategy optimal for all antibody-drug conjugates.…”
Section: Introductionmentioning
confidence: 99%